The causal relationship between gut microbiota and leukemia: a two-sample Mendelian randomization study - Chen, Guanjun; Kuang, Zheshu; Li, Fan; Li, Jianchang (Frontiers in Microbiology, 2023)
The association between gut microbiota and leukemia has been established, but the causal relationship between the two remains unclear. Methods: A bidirectional two-sample Mendelian randomization (MR) was used to analyze the causal relationship between gut microbiota and leukemia. Microbiome data (n=14,306) and leukemia (n=1,145) data were both sourced from European populations. Single nucleotide polymorphisms (SNPs) were selected as instrumental variables based on several criteria. We employed various MR methods, such as the inverse variance weighted (IVW) method, to evaluate the causal effect between exposure and outcomes and conducted sensitivity analyses to validate the heterogeneity and pleiotropy of the instrumental variables. Results: 5742 qualified instrumental variables were included. In the primary MR results, a total of 10 gut microbial taxa were associated with leukemia risk. Genus Blautia and genus Lactococcus are risk factors for acute lymphoblastic leukemia (genus Blautia odds ratio (OR):